The religious and cultural interaction and integration between Chinese Muslim Hui and non-Muslim in Han in China - Abdullah @ Chuah Hock Leng, Osman (s.n, 2012)
This paper is a research on the interaction between Chinese Muslim minority, the Hui with the non-Muslim majority, the Han in China. The finding prove that the Hui in China remain a marginalized group with little influence on political, economical, cultural and social affairs. It is also confirmed that for the Hui people, Islam is practiced as a comprehensive way of life unlike the Chinese non-Muslim. In China, the non-Muslim majority, the Han recognize the Hui people only as a minority ethnic group